Statin-induced anti-HMGCR myopathy: successful therapeutic strategies for corticosteroid-free remission in 55 patients - Meyer, Alain (Arthritis Res Ther, 2020)
OBJECTIVE: To describe successful therapeutic strategies in statin-induced anti-HMGCR myopathy. METHODS: Retrospective data from a cohort of 55 patients with statin-induced anti-HMGCR myopathy, sequentially stratified by the presence of proximal weakness, early remission, and corticosteroid and IVIG use at treatment induction, were analyzed for optimal successful induction and maintenance of remission strategies. RESULTS: A total of 14 patients achieved remission with a corticosteroid-free induction strategy (25%). In 41 patients treated with corticosteroids, only 4 patients (10%) failed an initial triple steroid/IVIG/steroid-sparing immunosuppressant (SSI) induction strategy. Delay in treatment initiation was independently associated with lower odds of successful maintenance with immunosuppressant monotherapy (OR 0.92, 95% CI 0.85 to 0.97, P = 0.015). While 22 patients (40%) presented with normal strength, only 9 had normal strength at initiation of treatment. CONCLUSION: While corticosteroid-free treatment of anti-HMGCR myopathy is now a safe option in selected cases, initial triple steroid/IVIG/SSI was very efficacious in induction. Delays in treatment initiation and, as a corollary, delays in achieving remission decrease the odds of achieving successful maintenance with an SSI alone. Avoiding such delays, most notably in patients with normal strength, may reset the natural history of anti-HMGCR myopathy from a refractory entity to a treatable disease.